Budaya Populer dan Konsumerisme: Studi Netnografi terhadap Perilaku Konsumtif Fandom ENGENE dalam Pembelian Merchandise - Stefani , Denis Hida Lutfiana (POPULIKA, 2025)
The hallyu or Korean wave phenomenon first popularized by journalists in Beijing related to the rapid spread of K-Pop popularity is now also experiencing massive spread in Southeast Asian countries, especially Indonesia. Fans who want to show their existence in supporting their idol artists are competing in buying and consuming merchandise products from the idol artists. This brings an attitude that leads to excessive consumerism in terms of fan loyalty to the idol artist. Engene is one of the K-Pop fandoms that increasingly shows its existence in the world of merchandise buying and selling. This research aims to understand the consumption pattern of Engene fandom by using netnography method and interview and observation. The results show that consumerism among fans is not only related to loyalty to idols, but also driven by feelings of wanting to be involved in the community, digital trends, and the phenomenon of fear of missing out (FOMO), which is the fear of being left out of the collective experience enjoyed by fellow fans. In addition, this study found that consumption patterns are not limited to the purchase of official merchandise, but also extend to the creative economy where fans act as producers and distributors of fandom-related products. This confirms that K-Pop popular culture has not only created a loyal fan base but also established a digital economic ecosystem supported by the active participation of online communities.